RI 8028 Electrophoretic and Filtration Studies of a Florida Phosphate Slime - Oleg Terichow (The National Institute for Occupational Safety and Health (NIOSH), 1975)
Electrophoretic mobility measurements were made by the Bureau of Mines on samples of a Florida phosphate slime to determine the optimum conditions of coagulation and settling in an aluminum sulfate solution. Addition of anthracite to promote mutual coagulation demonstrated the practicability of heterocoagulation by reduction of the repulsive effect of double layers. By proper selection of the electrolyte and its concentration, the reduction of the double layers to a net zero point of charge causes the predominance of Van der Waals' forces of attraction leading to the coagulation and rapid settling of both particle systems, as is predicted by the Derjaguin-Landau-Verwey-Overbeek theory of colloidal stability. Confirmation was found in the microfiltration tests where a modified Carman equation was applied to evaluate the specific filter bed resistance.